Kidney and Urinary Tract Involvement in Epidermolysis Bullosa: Is Routine Follow-Up Necessary? - Neslihan Cicek (Mattioli1885, 2021)
Background: Several renal and urinary tract complications have been reported in patients with epidermolysis bullosa.